Perilaku Rentenir dan Kegiatan Sosial Ekonomi: Studi Kasus Di Bo-gor - tinakartika rinda, rachmatullaily; Aminda, Renea Shinta (INOVATOR, 2020)
Loan sharks have an existence because loan sharks and borrower ecosystems are formed by mutual benefits, so research is conducted with the aim to discuss the influence of loan sharks on the socio-economic activities of the people of Bogor City. Despite having bad stereotypes in the eyes of the community, moneylenders have a special place among certain communities with a motive to meet their daily needs to meet secondary to tertiary needs because they offer unsecured soft loans compared to bank loan conditions that have to go through fairly complicated procedures. Research with descriptive qualitative type was carried out using a questionnaire method. Taking data using snowball sampling techniques and carried out on a sample of 211 people of the city of Bogor, with analysis techniques simple linear regression. The results of this study indicate that there is a very strong relationship between the socioeconomic activities of the community and activities carried out by moneylenders, where the largest economic activity for the allocation of education costs is the need and benefits of loan sharks.